Psychometric analysis of the repetitive behavior scale‐revised using confirmatory factor analysis in children with autism. Issue 9 (27th June 2019) - Hooker, Jessica L.; Dow, Deanna; Morgan, Lindee; Schatschneider, Christopher; Wetherby, Amy M.
Abstract : Research examining restricted and repetitive patterns of behavior or interests (RRB) in autism spectrum disorder (ASD) has increased our understanding of its contribution to diagnosis and its role in development. Advances in our knowledge of RRB are hindered by the inconsistencies in how RRB is measured. The present study examined the factor structure of the Repetitive Behavior Scale‐Revised (RBS‐R) in a sample of 350 children with ASD ages 2–9. Confirmatory factor analysis designed for items with categorical response types was implemented to examine six proposed structural models. The five‐factor model demonstrated the most parsimonious fit based on common overall fit indices that was further supported by examination of local model fit indicators, though, the four‐ and six‐factor models evidenced adequate‐to‐good fit as well. Examination of RRB factor score approaches indicated only minor differences between summed item subscale scores and extracted factor scores with regard to associations with diagnostic measures. All RRB subtypes demonstrated significant associations with cognitive functioning and adaptive behavior. Implications for future research validating the RBS‐R as a more extensive clinical measure of RRB in ASD are discussed. Autism Res 2019, 12: 1399–1410 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Repetitive behaviors are one of the two main symptoms of autism spectrum disorder (ASD). To better understand the role of repetitive behaviors, we must establish effective ways of measuring them. This study assessed the measurement qualities of the Repetitive Behavior Scale‐Revised (RBS‐R) in a sample of 350 children with ASD ages 2–9. We found that the RBS‐R measures multiple types of repetitive behaviors and that these behaviors are related to thinking ability and independence.